PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA KOPERASI SUMBER REJEKI REMBANG JAWA TENGAH - Oktaviani, Harmusa; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
The increasing number of cooperatives that exist among the people, make the cooperative should be able to compete and survive. Therefore Cooperative leaders and subordinates must cooperate in order to promote the company by increasing employee performance. To improve the performance of employees can be done in various ways one of them by creating a comfortable working environment for work and a strong organizational culture within the company.The study was performed using multiple linear regression analysis with SPSS 2. The samples in this study were all employees of the Cooperative Apex Sources with a number of Fortune 32 employees. Methods of data collection in this study was through a questionnaire distributed to 32 employees and data obtained from the company.The analysis showed that the variables work environment and organizational culture positive effect on employee performance with a coefficient of determination shows the value of Adjusted R Squareof 0.426. The results of the determination coefficient indicates that the work environment andorganizational culture in influencing employee performance by 42.6% while the rest is influenced by other variables.